NATO and International Crimes in the Kosovo Campaign – Can Bill Clinton and Tony Blair be Held Criminally Liable? - Niven, Peter (Victoria University of Wellington Law Review, 2003)
This paper examines the international law doctrines of command responsibility and sovereign immunity with respect to the potential liability of Bill Clinton and Tony Blair for any war crimes committed during “Operation Just Cause” in Kosovo in 1999. The paper discusses some of the alleged crimes committed by NATO forces during the operation to establish a context for the analysis of their potential liability under the doctrine of command responsibility. This doctrine makes commanders criminally liable if they knew, or should have known, of crimes committed or about to be committed by their subordinates and the commander fails to take necessary and reasonable measures to prevent the crimes or punish the perpetrators. Even if Clinton and Blair could be held criminally liable under this doctrine any prosecution faces the hurdle of sovereign immunity attaching to them as a former Head of State and current Head of Government.